Antiplasmid Potential of Kalanchoe Blossfeldiana Against Multidrug Resistance Pseudomonas Aeruginosa (Journal of the College of Basic Education, 2022)
This study is concerned with the isolation and identification of Pseudomonas aeruginosa from various clinical cases in human which include (burn, wound, and urine) that admitted to Emergency hospital and internal lab of teaching hospital in Erbil city. Forty isolates of P. aeruginosa from out of 120 samples were identified by using cultured, morphological and biochemical tests in addition to vitek machine. Antibiotic resistance test was used ,the isolates showed variation in their resistance; the highest resistance was for penicillin G with 85% while the lowest resistance was for ceftizoxime with 40% and for others ranged between 42.5-82.5%.On the other hand the isolates P9,P16, and P30 resisted all antibiotics under study . RCR was used to detect exotoxin A (ETA) structural gene sequence. The result revealed that 82.5% of the isolates were positive for ETA gene. Methanolic and aqueous crude extract of Kalanchoe blossfeldiana were used as medicinal plant as curing agent for the reduction of antibiotic resistance genes of P. aeruginosa isolate P9, this was done through determination of minimum inhibitory concentration (MIC) of this medicinal plant that used as curing agent which was 1800 µg/ml for aqueous extract and 1400 µg/ml for methanolic extract. The effect of MIC of methanolic extract on antibiotic resistance genes for isolate P9 was reduction of the resistance from 44-100% while the effect of MIC of aqueous extract on antibiotic resistance genes for isolate P9 was decreasing of the resistance from 36-86 % respectively and these results were supported through gel electrophoresis process.